PENILAIAN KINERJA RETURN PENGELOLAAN ASSET PERBANKAN (Studi Komparasi Pada Bank Umum Swasta Nasional Devisa dan Bank Asing) - Winarni, Winarni; Soemarso, Embun Duriany; Widiyati, Sri; Setianegara, R. Gunawan; Adhi, Nurseto (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
This study tried to analyse perfomance evaluation of banking asset management returns based on fundamental and macro factors from BUSND and foreign bank. This research also analyse the different of banking asset management Performance on BUSND and Foreign Bank. Multiple regression analysis method, F significance test, coefficient of determination and t significance test was used in This research. In order to find out the difference in asset return management between BUSND and foreign banks, a Chow-test was carried out.This study simultaneously found that fundamental factors proxied by the ratio of CAR, NIM, BOPO, LDR, and macro factors using SBI interest rates and exchange rates had a significant effect on ROA both in BUSND and foreign banks. In BUSND the independent variables for fundamental factors that have a significant effect on ROA are CAR, NIM, BOPO, and macro factors, namely the SBI interest rate, for foreign banks the results of the independent variables for fundamental factors that affect ROA are CAR, BOPO, and LDR . For the results of the Chow test, it was found that there was a significant difference between BUSND and foreign banks in terms of managing returns from the placement of bank assets (Return On Assets).